PS-056 How do you review a medication order? a FRANCE–QUEBEC comparison. (25th February 2017) - Dubois, S; Janes, A; Thibault, M; Leguelinel, G; Marson, C Roux; Kinowski, JM; Bussières, JF
Abstract : Background: Medication order review is a fundamental pharmacist activity. Several guidelines from different countries specify the validation elements required for medication order review in general but none of specify the optimal order to consider for these elements and taking into account its applicability in the hospital pharmacy. Purpose: The objective was to identify and justify similarities and differences between the medication order review processes in France and Quebec. Material and methods: This was a descriptive prospective study. 22 validation elements for medication order review were selected and sequenced from guidelines. An online survey was developed in three parts: (A) selection of validation elements in three scenarios—(1) centralised validation, (2) decentralised validation and (3) centralised validation by a pharmacist with a decentralised pharmacist present in patient care areas; (B) sequence of the 22 validation elements; and (C) level of agreement about medication order review statements. The survey was sent to hospital pharmacists at 2 teaching hospitals in Quebec and France. Results: The response rate was 60% (45/75: 23 in France; 22 in Quebec). For scenario (1), there was a significant difference between France and Quebec for 10 validation elements, 8 of these being more supported by Quebec respondents. For scenario (2), there was only 1 significant difference between France and Quebec. For scenario (3), nine elements were significantly different between France and Quebec, 5 of these being more supported by French respondents. These differences can be explained by local drug use process organisation and tools, current practices and personal prioritisation. For instance, a computerised prescriber order entry was used in the French hospital, but not in the Quebec one. Quebec pharmacists are used to having decentralised clinical pharmacists in patient care programmes but exposure of French pharmacists to this practice model is only emerging. Medication reconciliation has been required in Canada since 2008, while it has only started to be implemented in France. Conclusion: Medication order review practices are different between France and Quebec, in terms of validation elements considered by hospital pharmacists and their optimal sequence. Such differences can be explained by numerous factors, including tools used to prescribe and validate drug order and the presence of pharmacists in patient care areas. No conflict of interest